Chemically strengthened glass and method for producing the same

JP2025031256APending Publication Date: 2025-03-07AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023137365
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、優れた飛び石耐性および安全性を示す化学強化ガラスおよびその製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031256000003
    Figure 2025031256000003
  • Figure 2025031256000004
    Figure 2025031256000004
  • Figure 2025031256000001
    Figure 2025031256000001
Patent Text Reader

Abstract

To provide a chemically strengthened glass that exhibits excellent stone-chip resistance as well as high safety, and a method for producing the same.SOLUTION: A chemically strengthened glass has a thickness of more than 2 mm, a compression stress layer depth (DOC) of 500-1500 μm, and a maximum tensile stress (CTmax) of 20-59 MPa.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to chemically strengthened glass and a method for producing the same. [Background technology]

[0002] Mobile devices such as cars, trains, and drones, as well as outdoor sensors and security devices such as surveillance cameras, are equipped with multiple sensors with diverse functions. It is desirable to select a material for the protective member that protects the sensor that has high transmittance for visible light and excellent strength. Sensor modules that use glass as a protective member for protecting a sensor are known. For example, Patent Document 1 discloses a sensor module that uses chemically strengthened glass as a protective member.

[0003] Chemically strengthened glass is glass in which a compressive stress layer is formed on the surface thereof by a chemical strengthening treatment (ion exchange treatment) in which the glass is brought into contact with an inorganic salt composition such as sodium nitrate or potassium nitrate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 009336 Summary of the Invention [Problem to be solved by the invention]

[0005] There are three main types of strength required for the glass that protects the sensor. The first is resistance to flying stones. When a sensor is mounted on a mobile device, a foreign object such as a flying stone may collide with the sensor module while the device is moving. When an instantaneous impact is applied from the outside due to the collision of a flying stone or the like, the stress at the time of the collision is not alleviated and concentrated stress occurs, which may damage the glass and sensor, which are protective members. For this reason, the glass that protects the sensor must have excellent resistance to flying stones.

[0006] The second is the falling ball impact strength (hereinafter referred to as the falling ball strength). The glass protecting the sensor must be strong enough not to break easily when an object hits it or when the glass is dropped.

[0007] Thirdly, resistance to scratches caused by flying stones (hereinafter also referred to as scratch resistance) is required. Scratches on the glass surface caused by collisions with flying stones, etc., as well as cracks and deterioration of the appearance caused by the scratches, are problems, so scratch resistance that reduces the area and depth of scratches is required.

[0008] In order to increase resistance to flying stones, it is effective to form a compressive stress layer to a depth that is a certain percentage or more of the plate thickness. However, if chemical strengthening treatment is performed for a long period of time in order to form a compressive stress layer to a sufficient depth on chemically strengthened glass with a thickness of more than 2 mm, the total amount of compressive stress on the glass surface will increase, and the CT will correspondingly increase, exceeding the CT limit. In the event of breakage, the fragments will be very fine and will scatter over a wide area, posing a safety problem.

[0009] The present invention has been made in view of the above problems, and an object of the present invention is to provide a chemically strengthened glass exhibiting excellent stone chipping resistance and safety, and a manufacturing method thereof. [Means for solving the problem]

[0010] The present inventors have studied the above problems and have found that by performing a chemical strengthening treatment using a specific molten salt composition on chemically strengthened glass having a plate thickness of more than 2 mm, chemically strengthened glass having a specific stress profile can be obtained, and thus stone chip resistance and safety can be improved. As a result, the present inventors have completed the present invention.

[0011] One aspect of the present invention is as follows. [1] Chemically strengthened glass having a thickness of more than 2 mm, a compressive stress layer depth DOC of 500 to 1500 μm, and a maximum tensile stress CTmax of 20 to 59 MPa. [2] The chemically strengthened glass according to [1] above, wherein the maximum tensile stress CTmax is equal to or less than CTA calculated by the following formula (1), where t is the plate thickness in mm. CTA=-36.2ln(t)+97.7…(1) [3] Surface compressive stress value CS 0 The chemically strengthened glass according to the above [1] or [2], wherein the compressive strength is 1400 MPa or less. [4] Compressive stress value CS at a depth of 10 μm from the surface 10 The chemically strengthened glass according to any one of the above [1] to [3], having a compressive strength of 200 MPa or less. [5] Depth DOL when compressive stress value is 50MPa 50 The chemically strengthened glass according to any one of the above [1] to [4], wherein the grain size is 200 to 600 μm. [6] Compressive stress value CS at a depth of 400 μm from the surface 400 The chemically strengthened glass according to any one of the above [1] to [5], having a compressive strength of 30 to 100 MPa. [7] Compressive stress value CS at a depth of 500 μm from the surface 500 The chemically strengthened glass according to any one of the above [1] to [6], having a compressive strength of 15 to 80 MPa. [8] Compressive stress value CS at a depth of 600 μm from the surface 600 The chemically strengthened glass according to any one of the above [1] to [7], wherein the compressive strength is 0 to 50 MPa. [9] Compressive stress value CS at a depth of 400 μm from the surface 400 and the compressive stress value CS at a depth of 10 μm from the surface 10 Comparison with CS 400 / CS 10 The chemically strengthened glass according to any one of the above [1] to [8], wherein the value is 0.30 to 0.80.

[10] Compressive stress value CS at a depth of 600 μm from the surface 600 and the compressive stress value CS at a depth of 10 μm from the surface 10 Comparison with CS 600 / CS 10 The chemically strengthened glass according to any one of the above [1] to [9], wherein the value is 0.04 to 0.50.

[11] The chemically strengthened glass according to any one of the above [1] to

[10] , having a deep layer gradient of −0.25 to −0.01.

[12] The chemically strengthened glass according to any one of the above [1] to

[11] , wherein a ratio DOC / 1000t of the compressive stress layer depth DOC to 1000t is 0.15 to 0.30, where t is the plate thickness in mm.

[13] The integral of compressive stress in the thickness direction from a depth of 400 μm to a depth where the compressive stress value is zero (ICS) 400 The chemically strengthened glass according to any one of the above [1] to

[12] , wherein the modulus of elasticity is 3,000 to 60,000 MPa·μm.

[14] The integral of compressive stress in the thickness direction from a depth of 400 μm to a depth where the compressive stress value is zero (ICS) 400 The chemically strengthened glass according to any one of the above [1] to

[13] , wherein the ratio ICS400 / ICS of the integral ICS of the compressive stress value in the plate thickness direction from the surface to a depth position where the compressive stress value is zero is 0.13 to 0.90.

[15] The chemically strengthened glass according to any one of the above [1] to

[14] , which is a lithium-containing aluminosilicate glass.

[16] In mole percent based on oxide, SiO 2 52-75%, Al 2 O 3 1-20%, Na 2 O 1-20%, Li 2 The chemically strengthened glass according to any one of the above [1] to

[15] , containing 1 to 20% of O.

[17] The chemically strengthened glass according to any one of the above [1] to

[16] , which has a crack incidence rate of 20% or less as evaluated in accordance with the strength test method of ISO 20567-1 Test Method A.

[18] The chemically strengthened glass according to any one of the above [1] to

[17] , which has a crack incidence rate of 20% or less as evaluated in accordance with the strength test method of SAE J400.

[19] The chemically strengthened glass according to any one of the above [1] to

[18] , which is used as a protective member for an in-vehicle sensor.

[20] A method for producing chemically strengthened glass according to any one of the above [1] to

[19] , comprising contacting glass for chemical strengthening having a plate thickness of more than 2 mm with an inorganic salt composition containing 0.1 mass% or more of a lithium-containing inorganic salt.

[21] The method for producing chemically strengthened glass according to

[20] above, wherein the glass for chemical strengthening is contacted with the inorganic salt composition for 25 hours or longer.

[22] The method for producing chemically strengthened glass according to

[20] or

[21] above, wherein the glass for chemical strengthening is preheated before the glass for chemical strengthening is brought into contact with the inorganic salt composition.

[23] The method for producing chemically strengthened glass according to any one of

[20] to

[22] above, wherein the inorganic salt composition has a lithium nitrate content of 1 mass % or more and a sodium nitrate content of 80 mass % or more. Effect of the Invention

[0012] According to the present invention, it is possible to provide chemically strengthened glass exhibiting excellent resistance to flying stones and safety, and a manufacturing method thereof. [Brief description of the drawings]

[0013] [Figure 1] 1(a) and 1(b) are perspective views showing a configuration example in which chemically strengthened glass is used as a protective member. [Diagram 2] FIG. 2 is a schematic diagram for explaining a method for evaluating crack behavior. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described in detail, however, the present invention is not limited to the following embodiment and can be modified in any manner without departing from the gist of the present invention.

[0015] In this specification, the use of "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0016] In this specification, unless otherwise specified, the glass composition (content of each component) is expressed as a mole percentage based on oxide, and the mole percentage is simply represented as "%".

[0017] In this specification, the term "substantially free" means that the content is below the impurity level contained in raw materials, i.e., that the content is not intentionally added. Specifically, the content is, for example, less than 0.1%.

[0018] Hereinafter, "chemically strengthened glass" refers to glass after chemical strengthening treatment, and "glass for chemical strengthening" refers to glass before chemical strengthening treatment.

[0019] In this specification, the term "stress profile" refers to a representation of compressive stress values ​​with the depth from the glass surface as a variable. In the stress profile, tensile stress is represented as a positive value as the absolute value of negative compressive stress.

[0020] As used herein, the "depth of compressive stress layer (DOC)" refers to the depth (distance from the surface) from the glass surface to the position where the compressive stress value is zero. In the following, the surface compressive stress is calculated using CS 0 , the compressive stress value at a depth of 10 μm from the surface is CS 10 The compressive stress at a depth of 50 μm from the surface is CS 50 The compressive stress value at a depth of 400 μm from the surface is CS 400 The compressive stress value at a depth of 500 μm from the surface is CS 500 The compressive stress value at a depth of 600 μm from the surface is CS 600 , sometimes written as The depth at which the compressive stress value is 50 MPa is called the DOL. 50 It is written as follows. Additionally, "tensile stress (CT)" refers to the tensile stress value at a depth equal to 1 / 2 of the plate thickness t.

[0021] <Method of measuring stress profile> In this specification, stress profiles measured by a scattered light photoelastic stress meter (SLP) and a glass surface stress meter (FSM) are used. In this specification, unless otherwise specified, values ​​of compressive stress CS, tensile stress CT, compressive stress layer depth DOC, etc. refer to values ​​in the SLP stress profile. When the chemical strengthening treatment is performed in two or more stages and an inorganic salt composition containing a potassium-containing inorganic salt (potassium ion) is used in the second stage of the chemical strengthening treatment, the compressive stress value of the outermost surface of the chemically strengthened glass obtained in that case is the value measured by FSM.

[0022] An example of a method for measuring a stress profile using a scattered light photoelastic stress meter (SLP) is the method described in WO 2018 / 056121. The scattered light photoelastic stress meter (SLP) used is the SLP-2000 manufactured by Orihara Seisakusho Co., Ltd. Other measurement conditions (such as the software used) will be described later.

[0023] Examples of methods for measuring the stress profile using a glass surface stress meter (FSM) include the methods described in WO 2018 / 056121 and WO 2017 / 115811. The glass surface stress meter (FSM) used is the FSM6000-UV manufactured by Orihara Seisakusho Co., Ltd.

[0024] Each embodiment will be described below.

[0025] <Glass for chemical strengthening> <<First embodiment>> The glass for chemical strengthening of the first embodiment is preferably a lithium-containing aluminosilicate glass. A preferred composition of the lithium-containing aluminosilicate glass is, in mole percent on an oxide basis, SiO 2 52-75%, Al 2 O 3 1-20%, Na 2 O 1-20%, Li 2It is preferable that the oxygen content is 1 to 20%.

[0026] More preferably, the glass for chemical strengthening has, in mole percent on an oxide basis, SiO 2 52 to 75% Al 2 O 3 1 to 20% Li 2 1-20% O Na 2 1-20% O K 2 O 0 to 5%, MgO 0-20%, CaO 0-20%, SrO 0-20%, BaO 0-20%, ZnO 0-20% TiO 2 0 to 1% ZrO 2 0 to 8%, Y 2 O 3 Contains 0-5%.

[0027] <<Second embodiment>> The glass for chemical strengthening according to the second embodiment is preferably a glass containing crystalline matter. A preferred composition of the glass containing crystalline matter is, in mole percent on an oxide basis, SiO 2 40-70%, Li 2 O 10-35%, Al 2 O 3 A composition containing 1 to 15% of the above is preferred.

[0028] More preferably, the glass for chemical strengthening has, in mole percent on an oxide basis, SiO 2 40 to 70% Li 2 O 10-35%, Al 2 O 3 1 to 15% P 2 O 5 0.5 to 5%, ZrO 2 0.5 to 5%, B 2 O 3 0 to 10%, Na 2 O 0 to 10%, K 2 O 0 to 5%, SnO 2 Contains 0-4%.

[0029] <<Glass composition>> A preferred glass composition will now be described.

[0030] << <SiO 2 >>> In the glass for chemical strengthening according to the first embodiment, SiO 2 SiO is a component that forms the network structure of glass. It also increases chemical durability. 2 The content is preferably 52% or more, more preferably 56% or more, further preferably 60% or more, and particularly preferably 64% or more. On the other hand, in order to improve the melting property, SiO 2 The content is preferably 75% or less, more preferably 73% or less, further preferably 71% or less, and particularly preferably 69% or less.

[0031] In the glass for chemical strengthening according to the second embodiment, SiO 2 The content of SiO is preferably 40% or more. 2 The content is more preferably 45% or more, even more preferably 48% or more, still more preferably 50% or more, particularly preferably 52% or more, and most preferably 54% or more. On the other hand, in order to improve the melting property, SiO 2 The content is preferably 70% or less, more preferably 68% or less, further preferably 66% or less, and particularly preferably 64% or less.

[0032] << <Al 2 O 3 >>> In the glass for chemical strengthening according to the first embodiment, Al2 O 3 Al is an essential component that increases the surface compressive stress due to chemical strengthening. 2 O 3 The content is preferably 1% or more, more preferably 2% or more, further preferably 4% or more, and particularly preferably 6% or more. On the other hand, Al 2 O 3 The content is preferably 20% or less, more preferably 18% or less, further preferably 17% or less, further preferably 16% or less, and particularly preferably 15% or less, so that the devitrification temperature of the glass does not become too high.

[0033] In the glass for chemical strengthening according to the second embodiment, Al 2 O 3 The content is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, 5% or more, 5.5% or more, 6% or more, particularly preferably 6.5% or more, and most preferably 7% or more. On the other hand, Al 2 O 3 The content is preferably 15% or less, more preferably 12% or less, further preferably 10% or less, particularly preferably 9% or less, and most preferably 8% or less, so that the devitrification temperature of the glass does not become too high.

[0034] << <Na 2 O>>> In the glass for chemical strengthening according to the first embodiment, Na 2 O is a component that improves the melting property of glass and forms surface compressive stress by ion exchange. 2 The O content is preferably 1% or more, more preferably 2% or more, and further preferably 4% or more. Na 2 If there is too much O, the chemical strengthening properties will decrease, so Na 2 The O content is preferably 20% or less, more preferably 18% or less, further preferably 16% or less, and particularly preferably 14% or less.

[0035] In the glass for chemical strengthening according to the second embodiment, Na2 O is not essential, but when it is contained, it is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more. Na 2 If there is too much O, the Li 3 PO 4 It becomes difficult for crystals such as Na to precipitate, or the chemical strengthening properties decrease. 2 The O content is preferably 10% or less, more preferably 9% or less, further preferably 8% or less, particularly preferably 7% or less, and most preferably 3% or less.

[0036] << <K 2 O>>> In the glass for chemical strengthening according to the first embodiment, K 2 O is Na 2 Like O, it is a component that lowers the melting temperature of glass and also forms surface compressive stress through ion exchange. K 2 When O is contained, the content is preferably 0.1% or more, more preferably 0.3% or more, further preferably 0.4% or more, and particularly preferably 0.5% or more. K 2 If the O content is too high, the chemical strengthening properties or chemical durability decreases, so the O content is preferably 5% or less, more preferably 4.8% or less, even more preferably 4.5% or less, particularly preferably 4.2% or less, and most preferably 4.0% or less.

[0037] In the glass for chemical strengthening according to the second embodiment, K 2 When O is contained, the content is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. K 2 If the O content is too high, the chemical strengthening properties or chemical durability decreases, so the O content is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, particularly preferably 2% or less, and most preferably 1% or less.

[0038] << <Na 2 O+K2 O>>> In the glass for chemical strengthening according to the first embodiment, Na 2 O and K 2 Total content of Na 2 O+K 2 O improves the meltability of glass raw materials and, from the viewpoint of forming surface compressive stress by ion exchange, is preferably 1% or more, and more preferably 2% or more.

[0039] In the glass for chemical strengthening according to the second embodiment, Na 2 O and K 2 Total content of Na 2 O+K 2 O is preferably 1% or more, and more preferably 2% or more, in order to improve the meltability of the glass raw material.

[0040] << <Li 2 O>>> In the glass for chemical strengthening according to the first embodiment, Li 2 O is a component that forms surface compressive stress through ion exchange. 2 When O is contained, the content is preferably 1% or more, more preferably 2% or more, further preferably 4% or more, and particularly preferably 5% or more. On the other hand, Li is used to stabilize the glass. 2 The O content is preferably 20% or less, more preferably 17% or less, further preferably 16% or less, and particularly preferably 15% or less.

[0041] In the glass for chemical strengthening according to the second embodiment, Li 2 The O content is preferably 10% or more, more preferably 14% or more, even more preferably 15% or more, still more preferably 18% or more, particularly preferably 20% or more, and most preferably 22% or more. On the other hand, Li is used to stabilize the glass. 2 The O content is preferably 35% or less, more preferably 32% or less, further preferably 30% or less, particularly preferably 28% or less, and most preferably 26% or less.

[0042] << <K 2 O / R 2 O>>> In the glass for chemical strengthening according to the first embodiment, Li 2 O, Na 2 O and K 2 The total content of O (hereinafter referred to as R 2 O) against K 2 O content ratio K 2 O / R 2 It is preferable that O is 0.2 or less, since this can improve the chemical strengthening properties and chemical durability. K 2 O / R 2 O is more preferably 0.15 or less, and further preferably 0.10 or less. 2 O is preferably 10% or more, more preferably 12% or more, and even more preferably 15% or more. 2 The O content is preferably 20% or less, and more preferably 18% or less.

[0043] In the glass for chemical strengthening according to the second embodiment, Li 2 O, Na 2 O and K 2 The total content of O (hereinafter referred to as R 2 O) against K 2 O content ratio K 2 O / R 2 It is preferable that O is 0.2 or less, since this can improve the chemical strengthening properties and chemical durability. K 2 O / R 2 O is more preferably 0.15 or less, and further preferably 0.10 or less. 2 O is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. 2 The O content is preferably 29% or less, and more preferably 26% or less.

[0044] << <mgo>>> MgO is a component that stabilizes glass and also increases mechanical strength and chemical resistance. 2 O 3 It is preferable to include MgO when the content is relatively small, etc. When MgO is included, the content is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, and particularly preferably 4% or more. On the other hand, if too much MgO is added, the viscosity of the glass decreases and devitrification or phase separation tends to occur. The content of MgO is preferably 20% or less, more preferably 19% or less, further preferably 18% or less, and particularly preferably 17% or less.

[0045] CaO, SrO, BaO and ZnO are all components that improve the meltability of glass and may be contained.

[0046] << <cao>>> CaO is a component that improves the meltability of glass and improves the crushability of chemically strengthened glass, and may be contained. When CaO is contained, the content is preferably 0.5% or more, more preferably 1% or more, even more preferably 2% or more, particularly preferably 3% or more, and most preferably 5% or more. On the other hand, if the CaO content is too high, the ion exchange performance is significantly reduced, so the CaO content is preferably 20% or less. The CaO content is more preferably 14% or less, and further preferably 10% or less, 8% or less, 6% or less, 3% or less, and 1% or less in the following stepwise manner.

[0047] << <sro>>> SrO is a component that improves the meltability of glass and improves the crushability of chemically strengthened glass, and may be contained. When SrO is contained, the content is preferably 0.5% or more, more preferably 1% or more, even more preferably 2% or more, particularly preferably 3% or more, and most preferably 5% or more. On the other hand, if the SrO content is too high, the ion exchange performance is significantly reduced, so the SrO content is preferably 20% or less. The SrO content is more preferably 14% or less, and further preferably 10% or less, 8% or less, 6% or less, 3% or less, and 1% or less in the following stepwise order.

[0048] << <bao>>> BaO is a component that improves the meltability of glass and improves the crushability of chemically strengthened glass, and may be contained. When BaO is contained, the content is preferably 0.5% or more, more preferably 1% or more, further preferably 2% or more, particularly preferably 3% or more, and most preferably 5% or more. On the other hand, if the BaO content is too high, the ion exchange performance is significantly reduced, so the BaO content is preferably 20% or less. The BaO content is more preferably 15% or less, and further preferably 10% or less, 8% or less, 6% or less, 3% or less, and 1% or less in the following stepwise order.

[0049] << <zno>>> ZnO is a component that improves the meltability of glass and may be contained. When ZnO is contained, the content is preferably 0.25% or more, and more preferably 0.5% or more. On the other hand, if the ZnO content is too high, the weather resistance of the glass is significantly reduced, so the ZnO content is preferably 20% or less. The ZnO content is more preferably 14% or less, and further preferably 10% or less, 8% or less, 6% or less, 3% or less, and 1% or less in the following stepwise order.

[0050] << <ZrO 2 >>> ZrO 2 ZrO is a component that enhances mechanical strength and chemical durability, and is preferably contained since it significantly improves CS. 2 When contained, the content is preferably 0.5% or more, more preferably 0.7% or more, further preferably 1.0% or more, particularly preferably 1.2% or more, and most preferably 1.5% or more. On the other hand, in order to suppress devitrification during melting, ZrO 2 is preferably 8% or less, more preferably 7.5% or less, even more preferably 7% or less, and particularly preferably 6% or less. ZrO 2 If the content is too high, the viscosity decreases due to an increase in the devitrification temperature. In order to prevent deterioration of formability due to such a decrease in viscosity, when the forming viscosity is low, ZrO 2 The content is preferably 5% or less, more preferably 4.5% or less, and even more preferably 3.5% or less.

[0051] << <ZrO 2 / R 2 O>>> ZrO 2 / R 2 In order to enhance chemical durability, O is preferably 0.02 or more, more preferably 0.04 or more, even more preferably 0.06 or more, particularly preferably 0.08 or more, and most preferably 0.1 or more. ZrO 2 / R 2 O is preferably 0.2 or less, more preferably 0.18 or less, further preferably 0.16 or less, and particularly preferably 0.14 or less.

[0052] << <TiO 2 >>> TiO 2 is not essential, but if contained, it is preferably 0.05% or more, and more preferably 0.1% or more. On the other hand, in order to suppress devitrification during melting, TiO 2 The content is preferably 1% or less, more preferably 0.5% or less, and even more preferably 0.3% or less.

[0053] << <SnO 2 >>> SnO 2 is not essential, but when contained, it is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, in order to suppress devitrification during melting, SnO 2 The content is preferably 4% or less, more preferably 3.5% or less, further preferably 3% or less, and particularly preferably 2.5% or less.

[0054] << <Y 2 O 3 >>> Y 2 O 3 Y is a component that has the effect of preventing chemically strengthened glass from scattering when broken, and may be contained. 2 O 3 When contained, the content is preferably 0.3% or more, more preferably 0.5% or more, further preferably 0.7% or more, and particularly preferably 1.0% or more. On the other hand, in order to suppress devitrification during melting, Y 2 O 3 The content is preferably 5% or less, more preferably 4% or less.

[0055] << 2 O 3 >>> B 2 O​ 3 is a component that improves the chipping resistance and melting property of the glass for chemical strengthening or the chemically strengthened glass, and may be contained. 2 O 3 When contained, the content is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more, in order to improve the melting property. On the other hand, B 2 O 3 If the content is too high, striae may occur during melting, phase separation may occur, and the quality of the glass for chemical strengthening may deteriorate. Therefore, the content is preferably 10% or less. 2 O 3 The content is more preferably 8% or less, further preferably 6% or less, and particularly preferably 4% or less.

[0056] << <La 2 O 3 +Nb 2 O 5 +Ta 2 O 5 >>> La 2 O 3 , Nb 2 O 5 and Ta 2 O 5 Each of these is a component that makes it difficult for chemically strengthened glass to scatter into fragments when broken, and may be contained in order to increase the refractive index. If these are contained, La 2 O 3 , Nb 2 O 5 and Ta 2 O 5 The total content of (hereinafter, La 2 O 3 +Nb 2 O 5 +Ta 2 O 5 ) is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. In addition, La is added to prevent the glass from devitrifying during melting. 2 O 3 +Nb 2 O 5 +Ta 2 O 5 is preferably 4% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1% or less.

[0057] << <CeO 2 >>> In addition, the CEO 2 It may contain CeO 2 CeO can suppress coloring by oxidizing the glass. 2 When contained, the content is preferably 0.03% or more, more preferably 0.05% or more, and even more preferably 0.07% or more. CEO 2 The content is preferably 1.5% or less, and more preferably 1.0% or less, in order to increase transparency.

[0058] <<<Coloring ingredients>>> When the chemically strengthened glass is used after being colored, a coloring component may be added to the glass within a range that does not impede the achievement of the desired chemical strengthening characteristics. Examples of the coloring component include Co. 3 O 4 , MnO 2 , Fe 2 O 3 , NiO, CuO, Cr 2 O 3 , V 2 O 5 , Bi 2 O 3 , SeO 2 , Er 2 O 3 , Nd 2 O 3 Examples include: The total content of coloring components is preferably within the range of 1% or less. If it is desired to increase the visible light transmittance of the glass, it is preferable that these components are substantially not contained.

[0059] << <HfO 2 , Nb 2 O 5 and Ti 2 O 3 >>> To improve weather resistance to UV light exposure, HfO 2 , Nb 2 O 5 , Ti 2 O 3 When adding it for the purpose of improving weather resistance against ultraviolet light irradiation, HfO should be added in order to suppress the influence on other properties. 2 , Nb 2 O 5 and Ti 2 O 3 The total content of is preferably 1% or less, more preferably 0.5% or less, and even more preferably 0.1% or less.

[0060] <<<Clarifying agent>>> In addition, SO is used as a fining agent when melting glass. 3 The total content of components functioning as fining agents is preferably 2% or less, more preferably 1% or less, and even more preferably 0.5% or less, expressed as mass % on an oxide basis, since adding too much of them affects the strengthening properties. The lower limit is not particularly limited, but typically, the total amount is preferably 0.05% or more, expressed as mass% on an oxide basis.

[0061] SO as a clarifier 3 SO when using 3 If the content is too small, no effect is observed, so the content is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.1% or more, expressed as mass % on the oxide basis. In addition, SO is used as a clarifier. 3 SO when using 3 The content, expressed in mass % on an oxide basis, is preferably 1% or less, more preferably 0.8% or less, and further preferably 0.6% or less.

[0062] When Cl is used as a fining agent, if too much Cl is added, it affects physical properties such as strengthening characteristics, so the Cl content is preferably 1% or less, more preferably 0.8% or less, and even more preferably 0.6% or less, expressed as mass% on an oxide basis. Furthermore, when Cl is used as a fining agent, if the Cl content is too low, no effect is observed, so the Cl content is preferably 0.05% or more, more preferably 0.1% or more, and even more preferably 0.2% or more, expressed as mass% on an oxide basis.

[0063] SnO as a clarifier 2 When using SnO 2 The content, expressed in mass % on an oxide basis, is preferably 1% or less, more preferably 0.5% or less, and even more preferably 0.3% or less. In addition, SnO is used as a fining agent. 2 When using SnO 2 If the content is too small, no effect is observed, so the content is preferably 0.02% or more, more preferably 0.05% or more, and even more preferably 0.1% or more, expressed as mass % on the oxide basis.

[0064] << <P 2 O 5 >>> In the glass for chemical strengthening according to the first embodiment, P 2 O 5 It is preferable that P is not contained. 2 O 5 When it is contained, it is preferably 2.0% or less, more preferably 1.0% or less, and most preferably not contained.

[0065] In the glass for chemical strengthening according to the second embodiment, P 2 O 5 Li 3 PO 4 It is a structural component of crystals and is essential. 2 O 5 In order to promote crystallization, the content is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, particularly preferably 2% or more, and most preferably 2.5% or more. On the other hand, P 2 O 5 If the content is too high, phase separation occurs easily when melted, and acid resistance is significantly reduced. 2 O 5 The content is preferably 5% or less, more preferably 4.8% or less, further preferably 4.5% or less, and particularly preferably 4.2% or less.

[0066] << <As 2 O 3 and Sb 2 O 3 >>> As 2 O 3 It is preferable that it does not contain. Sb 2 O 3 When it is contained, it is preferably 0.3% or less, more preferably 0.1% or less, and most preferably not contained.

[0067] <<Method of measuring glass composition (content of each component)>> The glass composition (content of each component) of the glass for chemical strengthening and the chemically strengthened glass described below is determined by analysis using an electron probe micro analyzer (EPMA). More specifically, the analysis is performed using a JXA-8500F (manufactured by JEOL) as the EPMA under the following conditions. -Analyzing crystals: TAP crystal for Na, Si, Al, P, Sr, Zn, Sn, PETJ crystal for Ca, TAPH crystal for Mg, PETH crystal for K, Zr, Y, Ti, Ba Electron beam acceleration voltage: 15kV ·Irradiation electron beam current: 10nA Irradiation acquisition time: 10 s at peak position, 5 s at background position Analysis software used: JEOL software included with the device

[0068] <<Glass-ceramics>> The chemically strengthened glass may be a crystallized glass. In the case of crystallized glass, crystallized glass containing one or more crystals selected from the group consisting of lithium silicate crystals, lithium aluminosilicate crystals, zirconium-containing crystals, magnesium-containing crystals, and lithium phosphate crystals is preferred. As the lithium silicate crystal, lithium metasilicate crystal, lithium disilicate crystal, etc. are preferred. As the lithium phosphate crystal, lithium orthophosphate crystal and the like are preferable. As the lithium aluminosilicate crystal, a β-quartz solid solution, a β-spodumene crystal, a petalite crystal, or the like is preferable. The zirconium-containing crystal is preferably zirconia, a zirconia solid solution, etc. The zirconia solid solution may contain Y, Sn, etc. as a solid solution. As the magnesium-containing crystal, magnesium silicate and the like are preferred.

[0069] In order to increase the mechanical strength, the crystallization rate of the crystallized glass is preferably 10% or more, more preferably 15% or more, further preferably 20% or more, and particularly preferably 25% or more. In order to increase transparency, the crystallinity is preferably 70% or less, more preferably 60% or less, and particularly preferably 50% or less. A small crystallinity is also advantageous in that it is easy to bend and molded by heating. The crystallinity can be calculated from the X-ray diffraction intensity by the Rietveld method. The Rietveld method is described in "Crystal Analysis Handbook" edited by the Editorial Committee of the Crystallographic Society of Japan (Kyoritsu Shuppan, 1999, pp. 492-499).

[0070] <<Method of manufacturing glass for chemical strengthening>> In the method for producing glass for chemical strengthening, glass raw materials are appropriately mixed so as to obtain glass of a desired composition, and the glass is heated and melted in a glass melting furnace, and then the glass is homogenized by bubbling, stirring, adding a clarifier, etc., formed into a glass plate of a predetermined thickness, and slowly cooled. Alternatively, the glass may be formed into a plate shape by forming it into a block shape, slowly cooling it, and then cutting it.

[0071] Examples of methods for forming into a plate include the float method, the press method, the fusion method, and the down-draw method. In particular, when manufacturing a large glass plate, the float method is preferred. In addition, continuous forming methods other than the float method, such as the fusion method and the down-draw method, are also included. In order to form into a flat plate shape by the above-mentioned glass forming method, it is preferable that the chemically strengthened glass according to the present embodiment has a liquidus viscosity of 130 dPa·s or more.

[0072] The glass for chemical strengthening according to this embodiment usually has a plate shape, but may be a flat plate or a bent glass plate.

[0073] <Chemically strengthened glass> <<Glass composition>> In this embodiment, the glass composition of the chemically strengthened glass is the glass composition of a portion deeper than the compressive stress layer depth of the chemically strengthened glass, and is the same as the composition of the glass for chemical strengthening, except when extreme ion exchange treatment is performed. That is, in the chemically strengthened glass in the first embodiment, the matrix composition of the chemically strengthened glass is, in mole percent on an oxide basis, SiO 2 52-75%, Al 2 O 3 1-20%, Na 2 O 1-20%, Li 2 It is preferable that the oxygen content is 1 to 20%. In the chemically strengthened glass according to the second embodiment, the base composition of the chemically strengthened glass is, in mole percent based on oxides, SiO 2 40-70%, Li 2 O 10-35%, Al 2 O 3 A composition containing 1 to 15% of the above is preferred.

[0074] <<Thickness>> The chemically strengthened glass of the present embodiment has a plate thickness of more than 2 mm, preferably 2.5 mm or more, more preferably 3 mm or more, further preferably 4 mm or more, and particularly preferably 5 mm or more. By having a plate thickness of more than 2 mm, the strength is increased and excellent resistance to flying stones is exhibited. From the viewpoint of reducing weight, the plate thickness is preferably 7 mm or less, more preferably 6.6 mm or less, further preferably 6.2 mm or less, and particularly preferably 5.8 mm or less.

[0075] <<Method of manufacturing chemically strengthened glass>> <<<Process A>>> The method for producing chemically strengthened glass of the present embodiment includes a step of contacting chemically strengthened glass having a plate thickness of more than 2 mm with an inorganic salt composition containing 0.1 mass % or more of a lithium-containing inorganic salt (hereinafter also referred to as step A).

[0076] In step A, a chemical strengthening treatment (ion exchange treatment) is carried out. The chemical strengthening treatment is a treatment in which glass is brought into contact with an inorganic salt composition to replace metal ions in the glass with metal ions in the inorganic salt composition that have a larger ionic radius than the metal ions in the glass, thereby forming a compressive stress layer on the surface layer of the glass.

[0077] Methods for contacting glass with an inorganic salt composition include a method of applying a paste-like inorganic salt composition to glass, a method of spraying an aqueous solution of the inorganic salt composition onto glass, a method of immersing glass in an inorganic salt composition (also called a "molten salt") that has been melted by heating to a temperature equal to or higher than the melting point, etc. Among these, the method of immersing glass in a molten inorganic salt composition (molten salt) is preferred from the viewpoint of improving productivity.

[0078] As used herein, the term "inorganic salt composition" refers to a composition that contains an inorganic salt. Examples of inorganic salts contained in the inorganic salt composition include nitrates, sulfates, carbonates, and chlorides. Examples of nitrates include lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, rubidium nitrate, and silver nitrate. Examples of sulfates include lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, rubidium sulfate, and silver sulfate. Examples of carbonates include lithium carbonate, sodium carbonate, potassium carbonate, cesium carbonate, rubidium carbonate, and silver carbonate. Examples of chlorides include lithium chloride, sodium chloride, potassium chloride, cesium chloride, rubidium chloride, and silver chloride. These may be used alone or in combination of two or more kinds.

[0079] The main component of the inorganic salt composition is preferably a nitrate, more preferably sodium nitrate or potassium nitrate. Here, the term "main component" refers to a component whose content in the inorganic salt composition is 80% by mass or more.

[0080] Examples of the lithium-containing inorganic salt include lithium nitrate, lithium sulfate, lithium carbonate, and lithium chloride. One type may be used alone, or a plurality of types may be used in combination. Of these, the lithium-containing inorganic salt is preferably lithium nitrate.

[0081] The content of the lithium-containing inorganic salt refers to the mass ratio of the lithium-containing inorganic salt to the total weight of the inorganic salt composition. The content of the lithium-containing inorganic salt in the inorganic salt composition is 0.1% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 3% by mass or more, particularly preferably 4% by mass or more, and most preferably 6% by mass or more.

[0082] On the other hand, the content of the lithium-containing inorganic salt in the inorganic salt composition is preferably 20 mass % or less, more preferably 18 mass % or less, further preferably 16 mass % or less, particularly preferably 14 mass % or less, and most preferably 12 mass % or less.

[0083] The inorganic salt composition in step A may contain other inorganic salts in addition to the lithium-containing inorganic salt. Examples of other inorganic salts include potassium carbonate, potassium sulfate, potassium chloride, sodium nitrate, sodium carbonate, sodium sulfate, and sodium chloride, and among these, sodium nitrate is preferred.

[0084] In step A using the above-mentioned inorganic salt composition, for example, lithium ions in the glass are exchanged with sodium ions in the inorganic salt composition, and at the same time, sodium ions in the glass are exchanged with potassium ions in the inorganic salt composition.

[0085] To the inorganic salt composition in step A, silicic acid may be added as a pH lowering agent. When an inorganic salt composition containing nitrates is heated at high temperatures for a long period of time, the nitrates decompose, causing the pH of the molten inorganic salt composition (molten salt) to increase, and the OH - The glass network severing reaction caused by silicic acid can cause the appearance of the glass surface to deteriorate. The addition of silicic acid can suppress the increase in pH due to its neutralizing effect. As the silicic acid, silica gel or metasilicic acid is particularly preferable.

[0086] In step A, the temperature of the inorganic salt composition to be contacted with the glass for chemical strengthening is preferably 360°C or higher, more preferably 370°C or higher, further preferably 380°C or higher, and particularly preferably 390°C or higher. In addition, from the viewpoint of improving stone chip resistance, ball drop strength and scratch resistance while maintaining good appearance quality after ion exchange, the temperature of the inorganic salt composition is preferably 500°C or less, more preferably 480°C or less, even more preferably 465°C or less, and particularly preferably 455°C or less.

[0087] In step A, the time (contact time) for contacting the glass for chemical strengthening with the inorganic salt composition is, for example, 24 hours or more. From the viewpoint of increasing the surface compressive stress value, it is preferably 25 hours or more, more preferably 36 hours or more, even more preferably 48 hours or more, and particularly preferably 60 hours or more. From the viewpoint of improving resistance to flying stones and safety, the contact time is preferably 200 hours or less, more preferably 150 hours or less, further preferably 120 hours or less, and particularly preferably 100 hours or less.

[0088] The chemical strengthening treatment (ion exchange treatment) in the step A may be a one-stage treatment, or may be a two or more-stage treatment (multi-stage strengthening treatment) carried out under different conditions. When a multi-stage strengthening treatment is carried out, an inorganic salt composition containing 0.1 mass % or more of a lithium-containing inorganic salt may be used in either the first stage or the second stage or subsequent stages of ion exchange treatment.

[0089] When a multistage tempering treatment is carried out in step A, the method for producing chemically tempered glass of the present embodiment may include, after step A, a step of heating the glass for chemical tempering (hereinafter also abbreviated as step B).

[0090] <<<Process B>>> Step B is a step of heating the glass for chemical strengthening to a heating temperature of 100° C. or higher without contacting the glass with an inorganic salt composition. The heating temperature is more preferably 200° C. or higher, and further preferably 300° C. or higher. In order to improve working efficiency and prevent deformation of the glass for chemical strengthening, the heating temperature is preferably 500° C. or less. The heating time in step B is preferably 0.5 hours or more, more preferably 1 hour or more, and even more preferably 2 hours or more. From the viewpoint of work efficiency, the heating time in step B is preferably 12 hours or less.

[0091] <<<Preheating process>>> The method for producing chemically strengthened glass of the present embodiment may include a preheating step of heating the glass to be chemically strengthened before step A is carried out. The preheating step is a step of heating the glass for chemical strengthening to a preheating temperature of 100° C. or higher without contacting the glass with an inorganic salt composition. The preheating temperature is preferably 150° C. or higher, more preferably 200° C. or higher, and even more preferably 300° C. or higher. On the other hand, in order to prevent deformation and the like of the glass for chemical strengthening, the preheating temperature is preferably 500° C. or lower. From the viewpoint of performing heating in a sufficiently stable manner, the heating time in the preheating step is preferably 10 minutes or more, more preferably 30 minutes or more, and even more preferably 1 hour or more. From the viewpoint of work efficiency, the heating time in the preheating step is preferably 5 hours or less.

[0092] <<Stress profile>> << <doc>>> In this embodiment, the chemically strengthened glass has a compressive stress layer depth DOC of 500 μm or more, preferably 550 μm or more, more preferably 600 μm or more, and particularly preferably 650 μm or more, because the chemically strengthened glass exhibits excellent resistance to flying stones. For the same reason, the DOC is 1500 μm or less, preferably 1400 μm or less, more preferably 1300 μm or less, further preferably 1200 μm or less, and particularly preferably 1100 μm or less.

[0093] << <doc 1000t>>> In this embodiment, when the plate thickness of the chemically strengthened glass is t (unit: mm), the ratio (DOC / 1000t) of the compressive stress layer depth DOC to 1000t (plate thickness converted from mm to μm) is preferably 0.15 or more, more preferably 0.16 or more, even more preferably 0.18 or more, and particularly preferably 0.20 or more, because this provides better resistance to flying stones. For the same reason, the ratio of DOC to 1000t (DOC / 1000t) is preferably 0.30 or less, more preferably 0.27 or less, even more preferably 0.25 or less, particularly preferably 0.24 or less, and most preferably 0.23 or less.

[0094] << <DOL 50 >>> In the chemically strengthened glass of this embodiment, the depth DOL when the compressive stress value is 50 MPa 50 is preferably 200 μm or more, more preferably 280 μm or more, and even more preferably 350 μm or more. Meanwhile, DOL 50 is preferably 600 μm or less, more preferably 550 μm or less, and even more preferably 500 μm or less.

[0095] << <ctmax>>> In this embodiment, the chemically strengthened glass has a maximum tensile stress CTmax of 20 MPa or more, preferably 25 MPa or more, and more preferably 30 MPa or more, for reasons of excellent resistance to flying stones, falling ball strength, and scratch resistance. For reasons of superior safety, CTmax is 59 MPa or less, preferably 55 or less, and more preferably 50 MPa or less.

[0096] (CTA) The maximum value of the tensile stress CTmax is equal to or less than CTA (unit: MPa) represented by the following formula (1). In the following formula (1), t represents the sheet thickness (unit: mm) of the chemically strengthened glass, and ln(t) represents the natural logarithm with e as the base. By having CTmax less than or equal to CTA, DOC can be maximized while avoiding exceeding CT limits and maintaining safety. From the viewpoint of further avoiding the CT limit, the value obtained by subtracting the CTmax value from the CTA value is preferably 1 MPa or more, more preferably 3 MPa or more, and further preferably 5 MPa or more. CTA=-36.2ln(t)+97.7…(1)

[0097] << <ctave>>> In the chemically strengthened glass of this embodiment, the average tensile stress CTave is preferably 10 MPa or more, more preferably 15 MPa or more, and even more preferably 20 MPa or more. On the other hand, CTave is preferably 60 MPa or less, more preferably 55 or less, and even more preferably 50 MPa or less. The average value of the tensile stress CTave is the average value of the tensile stress in the region deeper than the compressive stress layer depth DOC.

[0098] << <CS 0 >>> <<< <CS 0 (SLP)>>>> In this embodiment, the surface compressive stress value CS of chemically strengthened glass measured by SLP 0 From the viewpoint of achieving a balance between compressive stress and tensile stress, (SLP) is preferably 200 MPa or less, more preferably 170 MPa or less, further preferably 150 Pa or less, and particularly preferably 120 MPa or less. On the other hand, C.S. 0 From the viewpoint of improving the bending strength, (SLP) is preferably 50 MPa or more, more preferably 70 MPa or more, and further preferably 90 MPa or more.

[0099] <<< <CS 0 (FSM)>>>> In this embodiment, the surface compressive stress value CS derived from K ions of chemically strengthened glass, which is measured by FSM, in chemically strengthened glass that has been subjected to two or more stages of chemical strengthening treatment. 0 (FSM) is preferably 1400 MPa or less, more preferably 1200 MPa or less, further preferably 1000 Pa or less, and particularly preferably 800 MPa or less. On the other hand, C.S. 0 From the viewpoint of improving the bending strength, (FSM) is preferably 50 MPa or more, more preferably 70 MPa or more, and further preferably 90 MPa or more.

[0100] << <CS 10 >>> In this embodiment, the compressive stress value CS at a depth of 10 μm from the surface of the chemically strengthened glass 10 is preferably 200 MPa or less, more preferably 180 MPa or less, and further preferably 150 MPa or less. On the other hand, C.S. 10 From the viewpoint of improving the bending strength, the compressive strength is preferably 50 MPa or more, more preferably 70 MPa or more, and further preferably 90 MPa or more.

[0101] << <CS 400 >>> In the chemically strengthened glass of this embodiment, the compressive stress value CS at a depth of 400 μm from the surface 400 is preferably 30 MPa or more, more preferably 35 MPa or more, and even more preferably 40 MPa or more. On the other hand, the compressive stress value CS 400 is preferably 100 MPa or less, more preferably 85 MPa or less, and even more preferably 70 MPa or less.

[0102] << <CS 500 >>> In the chemically strengthened glass of this embodiment, the compressive stress value CS at a depth of 500 μm from the surface 500 is preferably 15 MPa or more, more preferably 25 MPa or more, and even more preferably 35 MPa or more. Compressive stress value CS 500 is preferably 80 MPa or less, more preferably 70 MPa or less, and even more preferably 60 MPa or less.

[0103] << <CS 600 >>> In the chemically strengthened glass of this embodiment, the compressive stress value CS at a depth of 600 μm from the surface 600 is preferably 0 MPa or more, more preferably 10 MPa or more, and even more preferably 20 MPa or more. On the other hand, the compressive stress value CS 600 is preferably 50 MPa or less, more preferably 45 MPa or less, and even more preferably 40 MPa or less.

[0104] << <CS 400 / CS 10 >>> In the chemically strengthened glass of this embodiment, the compressive stress value CS 400 and compressive stress value CS 10 Ratio to (CS 400 / CS 10 ) is preferably 0.30 or more, more preferably 0.40 or more, and even more preferably 0.50 or more. On the other hand, the ratio (CS 400 / CS 10 ) is preferably 0.80 or less, more preferably 0.75 or less, and even more preferably 0.70 or less.

[0105] << <CS 600 / CS 10 >>> In the chemically strengthened glass of this embodiment, the compressive stress value CS 600 and compressive stress value CS 10 Ratio to (CS 600 / CS 10 ) is preferably 0.04 or more, more preferably 0.10 or more, and even more preferably 0.18 or more. On the other hand, the ratio (CS 600 / CS 10 ) is preferably 0.50 or less, more preferably 0.45 or less, and even more preferably 0.40 or less.

[0106] << <ics>>> In the chemically strengthened glass of this embodiment, the integral value ICS of the compressive stress value in the plate thickness direction from the surface to a depth position where the compressive stress value is zero is preferably 25,000 MPa μm or more, more preferably 30,000 MPa μm or more, and even more preferably 34,000 MPa μm or more, from the viewpoint of achieving a balance between compressive stress and tensile stress. On the other hand, for reasons of excellent safety, the ICS is preferably 47,000 MPa·μm or less, more preferably 46,000 MPa·μm or less, and even more preferably 45,000 MPa·μm or less.

[0107] << <ICS 400 >>> In the chemically strengthened glass of this embodiment, the integral value ICS of the compressive stress value in the plate thickness direction from the position at a depth of 400 μm to the depth position where the compressive stress value is zero 400 is preferably 3,000 MPa·μm or more, more preferably 5,000 MPa·μm or more, and even more preferably 7,000 MPa·μm or more. On the other hand, ICS 400 is preferably 60,000 MPa·μm or less, more preferably 55,000 MPa·μm or less, and even more preferably 50,000 MPa·μm or less.

[0108] << <ICS 400 / ICS>>> In the chemically strengthened glass of this embodiment, ICS 400 The ratio of the integral value ICS of the compressive stress value in the thickness direction from the surface to the depth position where the compressive stress value is zero to the compressive stress value (ICS 400 / ICS) is preferably 0.13 or more, more preferably 0.20 or more, and even more preferably 0.28 or more. On the other hand, the ratio (ICS 400 / ICS) is preferably 0.90 or less, more preferably 0.85 or less, and even more preferably 0.80 or less.

[0109] <<<Deep Tilt>>> In the chemically strengthened glass of the present embodiment, the deep layer gradient is preferably −0.01 or less, more preferably −0.05 or less, and further preferably −0.10 or less. On the other hand, the deep layer gradient is preferably −0.25 or more, more preferably −0.22 or more, and even more preferably −0.20 or more.

[0110] The deep layer gradient of chemically strengthened glass is calculated using SLP. 50 and the ratio of DOC minus 50 (DOC-50) (CS 50 / (DOC-50)).

[0111] <<<Surface gradient>>> In the chemically strengthened glass of the present embodiment, the surface layer slope is preferably 400 or less, more preferably 350 or less, and still more preferably 300 or less. On the other hand, the deep layer gradient is preferably 100 or more, more preferably 150 or more, and even more preferably 200 or more.

[0112] The surface layer slope of chemically strengthened glass is calculated using FSM. 0 and DOL ratio (CS 0 / DOL). Here, DOL is the depth of the compressive stress layer derived from potassium ions (unit: μm) determined using FSM.

[0113] <<Crack occurrence rate>> The chemically strengthened glass of the present embodiment has a cracking rate evaluated according to the strength test method of ISO 20567-1 Test Method A of preferably 20% or less, more preferably 18% or less, even more preferably 15% or less, and particularly preferably 13% or less. By having a cracking rate of 20% or less, it is possible to more effectively improve resistance to flying stones. When determining the cracking rate, n is 3 or more.

[0114] The chemically strengthened glass of the present embodiment has a cracking rate evaluated according to the strength test method of SAE J400 of preferably 40% or less, more preferably 30% or less, even more preferably 20% or less, and particularly preferably 13% or less. By having a cracking rate of 40% or less, it is possible to more effectively improve resistance to flying stones. When determining the cracking rate, n is 3 or more.

[0115] <<Applications>> The chemically strengthened glass of the present embodiment can be used, for example, as a protective member for a sensor. Examples of the sensor include sensors mounted on mobile devices such as cars and drones; outdoor sensors; and sensors mounted on surveillance cameras. Since the chemically strengthened glass of the present embodiment exhibits excellent resistance to flying stones, it is preferably used as a protective member for a sensor mounted on a mobile device, more preferably as a protective member for an in-vehicle sensor.

[0116] 1(a) and 1(b) are perspective views showing a configuration example in which chemically strengthened glass is used as a protective member.

[0117] In FIG. 1(a), chemically strengthened glass is used for a lid portion 10 of a cylindrical protective member 1 that houses a sensor 20 (including a camera 30) mounted in a mounting portion 5. In the protective member 1, the support portion 2 that supports the lid portion 10 may also be made of chemically strengthened glass, but metal such as stainless steel or anodized aluminum may also be used.

[0118] In FIG. 1(b), chemically strengthened glass is used as a hemispherical protective member 1 that houses a sensor 20 mounted on a mounting portion 5. In FIG.

[0119] The shape of the protective member 1 is not limited to a cylindrical shape or a hemispherical shape, and may also be a cylindrical shape, a prismatic shape, a hemispherical polyhedral shape, or the like.

[0120] The protective member 1 may be formed by bonding together a plurality of pieces of chemically strengthened glass. For example, in FIG. 1(a), when chemically strengthened glass is used not only for the lid part 10 but also for the support part 2, an adhesive layer can be formed between the lid part 10 and the support part 2 to bond them together. EXAMPLES

[0121] The present invention will be described below with reference to examples, but the present invention is not limited thereto. Below, Examples 1 to 5 are working examples, Examples 6 to 12 are comparative examples, and Example 13 is a reference example.

[0122] <Preparation of glass for chemical strengthening> Glass raw materials were mixed so that the glass composition expressed in mole % based on oxides would be as follows, and weighed out to give 400 g of glass. The mixed raw materials were then placed in a platinum crucible and placed in an electric furnace at 1500 to 1700° C. for about 3 hours to melt, degas, and homogenize the mixture, thereby obtaining molten glass. The obtained molten glass was poured into a mold and kept at a temperature near the glass transition point (714° C.) for about 1 hour, and then cooled to room temperature at a rate of 100° C. / min to obtain a glass block. From the obtained glass block, a glass plate (chemically strengthened glass A or B) having a size of plate thickness (unit: mm)×50 mm×50 mm shown in Table 1 below was produced.

[0123] <<Chemically strengthened glass A>> SiO 2 : 66.2%, Al 2 O 3 :11.2%, MgO:3.1%, CaO:0.2%, ZrO 2 :1.3%, Y 2 O 3 : 0.5%, Li 2 O: 10.4%, Na 2 O: 5.6%, K 2 O: 1.5%

[0124] <<Chemically strengthened glass B>> SiO 2 : 64.2%, Al 2 O 3 :8.0%, MgO:10.5%, CaO:0.1%, SrO:0.1%, BaO:0.1%, ZrO 2 : 0.5%, Na 2 O: 12.5%, K 2 O: 4.0%

[0125] The glass compositions of the obtained glass sheets (Glasses A and B for chemical strengthening) were determined by the above-mentioned method, and were found to be consistent with the above-mentioned compositions. The value obtained by subtracting the total content of each component from 100% was used as the Li (Li 2 O) content.

[0126] <Production of chemically strengthened glass> The glass plate obtained above was subjected to a chemical strengthening treatment (step A) by immersing it in a molten salt composition under the conditions shown in Table 1 below. In Example 3, a two-stage chemical strengthening treatment was carried out. In all the examples, before carrying out the chemical strengthening treatment, the glass plate was heated at a preheating temperature of 350° C. for 15 minutes (preheating step). In Example 13, the chemically strengthened glass A was used as it was without being subjected to a chemical strengthening treatment.

[0127] <Evaluation of chemically strengthened glass> The obtained chemically strengthened glass was subjected to various evaluations. In Table 1 below, "-" indicates that the evaluation was not performed, and those that could not be measured were recorded as 0.

[0128] <<Measurement of stress profile>> The stress of the chemically strengthened glass was measured using a scattered light photoelastic stress meter (SLP-2000 manufactured by Orihara Seisakusho Co., Ltd.) according to the method described in International Publication No. 2018 / 056121. In addition, the stress profile was calculated using the attached software [SlpV+Ver.2021.07.13.001] of the scattered light photoelastic stress meter. However, in Example 3 in which a two-stage chemical strengthening treatment was performed, the stress of the chemically strengthened glass was measured using a glass surface stress meter (FSM6000-UV manufactured by Orihara Manufacturing Co., Ltd.) by the method described in International Publication No. 2018 / 056121.

[0129] The function used to obtain the stress profile was σ(x)=[a 1 ×erfc(a 2 ×x)+a 3 ×erfc(a 4 ×x)+a 5 ]. i ( i = 1 to 5) are fitting parameters, and erfc is the complementary error function. The complementary error function is defined by the following equation.

[0130]

number

[0131] In the evaluation in this specification, the fitting parameters were optimized by minimizing the residual sum of squares between the obtained raw data and the above function. The measurement processing conditions were single shot, and the measurement area processing adjustment items were selected as follows: edge method on the surface, 6.0 μm for the inner surface end, automatic for the inner left and right ends, automatic (center of the sample thickness) for the inner deep end, and the extension of the phase curve to the center of the sample thickness was selected as a fitting curve.

[0132] From the obtained stress profile, various parameters such as the compressive stress layer depth DOC and the maximum tensile stress CTmax were obtained. The results are shown in Table 1 below.

[0133] <<Resistance to flying stones>> <<<Crack occurrence rate (ISO)>>> A stone chipping test was conducted under the following conditions in accordance with the strength test method of ISO 20567-1 Test Method A, and the crack occurrence rate was calculated (n=10). The results are shown in Table 1 below. Stepping stones: Chilled iron grit Stone size: 3.55~5mm ·Injection amount: 500g Injection pressure: 100kPa Sample installation angle: 54° ·Injection time: 8~12s Number of shots: 2 Sample impact area: 40mm x 40mm

[0134] <<<Crack occurrence rate (SAE)>>> A stone chipping test was conducted under the following conditions in accordance with the SAE J400 strength test method, and the crack occurrence rate was calculated (n=5). The results are shown in Table 1 below. Stepping stones: River gravel Stone size: 5~13mm ·Injection volume: 0.473L Injection pressure: 0.483MPa Sample installation angle: 90° ·Injection time: 10s Number of shots: 1 Sample impact area: 40mm x 40mm

[0135] The crack occurrence rate (unit: %) was calculated as follows. Crack occurrence rate: 100 x (number of samples cracked in the stone chipping test / total number of samples evaluated) - Judgment of sample cracks: There should be cracks extending beyond the scope of individual scratches on the sample surface after the stone chipping test.

[0136] <<Safety (cracking behavior)>> The cracking behavior of the chemically strengthened glass was evaluated as follows using a carbide automatic punch manufactured by TRUSCO.

[0137] FIG. 2 is a schematic diagram for explaining a method for evaluating crack behavior. As shown in FIG. 2, a super-hard automatic punch 410 was placed at the center of a surface 210 of a 50 mm×50 mm piece of chemically strengthened glass 200 placed on a test stand 400, and the chemically strengthened glass 200 was pressed vertically under a static load until it broke.

[0138] If the chemically strengthened glass did not break, the above operation was repeated while increasing the load by 1 kgf increments until it broke. In Table 1 below, if the number of pieces of broken glass when the chemically strengthened glass broke was 2 to 9, it was marked with "◎", if it was 10 to 19, it was marked with "○", and if it was 20 or more, it was marked with "×". The fewer the number of fragments, the greater the safety rating.

[0139] [Table 1]

[0140] <Summary of evaluation results> As shown in Table 1 above, Examples 1 to 5 exhibited superior stone chip resistance compared to Examples 8 to 13. Also, Examples 1 to 5 exhibited superior cracking behavior (i.e., superior safety) compared to Examples 6 to 8 and Examples 11 to 12. [Explanation of symbols]

[0141] 1 Protective material 2 Support part 5. Mounting section 10 Lid 20 Sensors 30 Camera 200 Chemically strengthened glass 210 Chemically strengthened glass surface 400 Test bench 410 Carbide automatic punch 411 Tip< / ics> < / ctave> < / ctmax> < / doc> < / doc> < / zno> < / bao> < / sro> < / cao> < / mgo>

Claims

1. Chemically strengthened glass having a plate thickness of more than 2 mm, a compressive stress layer depth DOC of 500 to 1500 μm, and a maximum tensile stress CTmax of 20 to 59 MPa.

2. 2. The chemically strengthened glass according to claim 1, wherein the maximum value CTmax of the tensile stress is equal to or less than CTA calculated by the following formula (1), when the plate thickness is t in mm. CTA=-36.2ln(t)+97.7...(1)

3. Surface compressive stress value CS 0 The chemically strengthened glass according to claim 1, wherein the strength of the glass is 1400 MPa or less.

4. Compressive stress value CS at a depth of 10 μm from the surface 10 The chemically strengthened glass according to claim 1, wherein the strain is 200 MPa or less.

5. Depth DOL when compressive stress value is 50 MPa 50 The chemically strengthened glass according to claim 1, wherein the thickness is 200 to 600 μm.

6. Compressive stress value CS at a depth of 400 μm from the surface 400 The chemically strengthened glass according to claim 1, wherein the compressive strength is 30 to 100 MPa.

7. Compressive stress value CS at a depth of 500 μm from the surface 500 The chemically strengthened glass according to claim 1, wherein the compressive strength is 15 to 80 MPa.

8. Compressive stress value CS at a depth of 600 μm from the surface 600 The chemically strengthened glass according to claim 1, wherein the strain is 0 to 50 MPa.

9. Compressive stress value CS at a depth of 400 μm from the surface 400 and the compressive stress value CS at a depth of 10 μm from the surface 10 Compared to CS 400 / CS 10 The chemically strengthened glass according to claim 1, wherein the refractive index is 0.30 to 0.

80.

10. Compressive stress value CS at a depth of 600 μm from the surface 600 and the compressive stress value CS at a depth of 10 μm from the surface 10 Relative to CS 600 / CS 10 The chemically strengthened glass according to claim 1, wherein the refractive index is 0.04 to 0.

50.

11. The chemically strengthened glass according to claim 1, wherein the deep layer slope is −0.25 to −0.

01.

12. 2. The chemically strengthened glass according to claim 1, wherein a ratio DOC / 1000t of the compressive stress layer depth DOC to 1000t is 0.15 to 0.30, when the plate thickness is t in mm.

13. The integral value ICS of the compressive stress value in the thickness direction from the position at a depth of 400 μm to the position at a depth where the compressive stress value is zero 400 The chemically strengthened glass according to claim 1, wherein the modulus of elasticity is 3,000 to 60,000 MPa μm.

14. The integral value ICS of the compressive stress value in the thickness direction from the position at a depth of 400 μm to the position at a depth where the compressive stress value is zero 400 The ratio ICS of the integral value ICS of the compressive stress value in the thickness direction from the surface to the depth position where the compressive stress value is zero 400 The chemically strengthened glass according to claim 1, wherein / ICS is 0.13 to 0.

90.

15. The chemically strengthened glass according to claim 1 , which is a lithium-containing aluminosilicate glass.

16. In terms of oxide mol%, SiO 2 52 to 75%, Al 2 O 3 1 to 20%, Na 2 1-20% O, Li 2 The chemically strengthened glass according to claim 1, containing 1 to 20% O.

17. The chemically strengthened glass according to claim 1, wherein the crack occurrence rate evaluated in accordance with the strength test method of ISO 20567-1 Test Method A is 20% or less.

18. The chemically strengthened glass according to claim 1, having a crack occurrence rate evaluated in accordance with the strength test method of SAE J400 of 20% or less.

19. The chemically strengthened glass according to claim 1, which is used as a protective member for an in-vehicle sensor.

20. A method for producing chemically strengthened glass according to any one of claims 1 to 19, A method for producing chemically strengthened glass, comprising contacting a chemically strengthened glass having a plate thickness of more than 2 mm with an inorganic salt composition having a lithium-containing inorganic salt content of 0.1 mass% or more.

21. The method for producing chemically strengthened glass according to claim 20, wherein the time for which the glass for chemical strengthening is contacted with the inorganic salt composition is 25 hours or longer.

22. The method for producing chemically strengthened glass according to claim 20, wherein the glass for chemical strengthening is preheated before the glass for chemical strengthening is contacted with the inorganic salt composition.

23. The method for producing chemically strengthened glass according to claim 20, wherein the inorganic salt composition has a lithium nitrate content of 1 mass% or more and a sodium nitrate content of 80 mass% or more.

Citation Information

Patent Citations

  • Sensor module and protective glass

    WO2019009336A1